Realising the potential of health needs assessments - Anstey, Matthew; Burgess, P.; Angus, L. (CSIRO Publishing, 2018)
Population-level assessment and planning has traditionally been the role of public health departments but in establishing Primary Health Networks (PHNs), the Australian Government has instituted a new mechanism for identifying community needs and commissioning services to meet those needs. If PHNs are to achieve the vision of nimble organisations capable of identifying and addressing local health needs via integrated health and social services, several things need to occur. First, PHN funding schedules must become more flexible. Second, the Federal health department must maintain an open dialogue with PHNs, permit waivers in funding schedules to suit local conditions and be prepared to back innovations with seed investment. Third, health data exchange and linkage must be accelerated to better inform community needs assessments and commissioning. Finally, PHNs must be encouraged and supported to develop collaborations both within and outside the health sector in order to identify and address a broad set of health issues and determinants. By following these principles, PHNs may become leading change agents in the Australian healthcare system.